Dual-band graphene-induced plasmonic quarter-wave platemetasurface in the near infrared - Owiti, Edgar; Yang, Hanning; Ominde, Calvine; Sun, Xiudong (Springer Berlin Heidelberg, 2017)
Weak graphene plasmon is a key challenge for graphene-based meta surfaces in the visible and near-in-frared regions. In this study, we have numerically designed and demonstrated a tunable, ultra thin, hybrid dual-band quarter-wave plate meta surface, which comprises of graphene, metal, and glass. Tunable birefringence has been obtained through the number of layers of graphene, its Fermi energy, metal dimensions, and the periodicity. The design also achieves a 95% polarization conversion ratio from a linear state to a circular state with a near unity value of ellipticity at a design wavelength in the near-infrared.The ultra thin thickness of the structure, 0.1k, and an embedding glass makes the structure compact and easily integrable for photonic-sensing application in the near-infrared.